Pulmonary Alveolar Microlithiasis: A Rare Lung Disease Diagnosed by Thoracoscopic Lung Biopsy - Rajbhandari, G L (Medical Journal of Shree Birendra Hospital, 2005)
Pulmonary Alveolar Microlithiasis: A Rare Lung Disease Diagnosed by Thoracoscopic Lung Biopsy